Inovasi Produk Pangan Roti Tawar Susu Kambing Etawa Sebagai Alternatif Makanan yang Mengandung Kalsium - Fahmi Farizzi Shiddiq; Linda Riski Sefrina; Eka Andriani (Universitas Respati Indonesia, 2023)
Introduction : Calcium intake of Indonesians is still low, at 342 mg/day. Lack of calcium intake during growth can cause several disorders in the bones, namely impaired bone growth, bones become less strong, easily bent, and brittle. Goat's milk has the potential to be used as a source of calcium. Goat's milk can contribute 32.6% calcium and 27.0% phosphorus of the required daily needs. Objective: to develop white bread products with the addition of Etawa goat's milk as an alternative to increase the consumption of foods containing calcium. Methods: This study used an experimental method (experimental) using a factorial Completely Randomized Design (CRD) research design with 5 levels of treatment, namely the addition of 10%, 15%, 20%, and 25% concentration of Etawa goat's milk from the composition of wheat flour. Result : Determination of the best formula using the Bayes method shows the best formula is the formula with the addition of 15%. The proximate test and calcium content test showed that white bread with the addition of 15% Etawa goat's milk from wheat flour had a water content of 32.69%, ash content of 1.87%, fat content of 8.44, carbohydrate content of 48.06. %, and calcium levels 21.52 mg. Conclusion: the preferred formula is plain bread formula with the addition of 15% Etawa goat's milk from wheat flour composition. The calcium content of the 15% addition formula is 21.51 mg/100gram. The calcium content cannot be claimed as a calcium source food because it is less than 15% ALG. Keywords: calcium consumption, white bread, Etawa goat's milk.